Kajian Literatur tentang Doktrin Keselamatan (Soteriologi) - Widya Salza Angelica1; Uci Pebrianti; Riski Yurisgio; Sarmauli (Indo Publishing, 2025)
This study aims to examine the literature on the Doctrine of Salvation (Soteriology). This research uses a qualitative method with a literature review approach. The study draws on various secondary data sources and transforms them into narratives. The results of the study reveal that the doctrine of salvation (soteriology) is a fundamental teaching that not only provides a theological understanding of how humans are saved but also guides the Christian life as a whole. It teaches that salvation is God's perfect work through Christ, received through faith, and produces a new life that bears fruit in love, service, and hope. Salvation provides meaning, strength, and purpose in life, while also providing the basis for the eternal hope that believers will ultimately live in happiness and peace with God forever.